Introducing Autodesk Maya 2012 - Derakhshani, Dariush (Indianapolis, Ind. Wiley Publishing, 2011)
A practical, step-by-step guide to Maya 2012 This book is the ideal primer to getting started with Maya, the premier 3D animation and effects software used in movies, visual effects, games, cartoons, short films, and commercials. You'll learn the Maya interface and the basics of modeling, texturing, animating, and visual effects
Include Illustration and Index
Keywords: Three-dimensional display systems -- Computer graphics -- Computer animation